Learner-Generated and Instructor-Provided Graphic Organizers as Aids to Learning from Text: A Meta-Analysis - Ponce-Arias, H; Mendez, E (Springer, 2025)
Graphic organizers are spatial representations of key textual information—such as matrices, flowcharts, or hierarchies—that can support learning through two primary approaches: as a generative learning activity, where students construct their own organizers while reading, or as an instructional design feature, where organizers are provided by the instructor. This meta-analysis evaluated the effectiveness of both approaches. For learner-generated graphic organizers, the analysis yielded average effect sizes of g + = 0.59 for memory outcomes (p <.001, k = 44) and g + = 0.63 for comprehension outcomes (p <.001, k = 68), favoring the generative use of organizers. For instructor-provided graphic organizers, effect sizes were g + = 0.70 for memory (p <.001, k = 37) and g + = 0.53 for comprehension (p <.001, k = 49), indicating benefits as an instructional aid. Moderator analyses showed that the effectiveness of learner-generated graphic organizers varied by intervention setting (lab vs. classroom), test type (researcher-developed vs. standardized), educational level (elementary, secondary, or college), and year of publication, whereas no significant moderators emerged for instructor-provided organizers. Evidence of publication bias and small-study effects—particularly in classroom-based studies—suggests that reported effect sizes may be inflated. Overall, these findings provide strong empirical support for the use of graphic organizers in educational contexts, highlighting their dual role as both a generative learning strategy and an instructional support consistent with the principles of generative learning theory. © The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature 2025.